Pentingnya Penerapan Digital Marketing dan Penguatan UMKM: (Studi Kasus Pada Dusun Dawungan dan Dadapan di Desa Ngadirejo) - Muhammad Agustian Sakha; Hironimus Steven Permana; Faiz Nawawi; Galang Adipura; Dwi Puji Haryanto; Luwes Dwi Triani; Malkah Melia Oktaviana; Almaas Raaffina Putri; Zahra Aulia; Audya Mulia Nurfadilah (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
The community service program conducted by the KKN II Team of Ngadirejo Village aims to overcome marketing problems in businesses through digital marketing socialization and strengthening MSMEs in Dawungan and Dadapan Hamlets, Ngadirejo Village. This activity includes two main methods, namely digital marketing socialization to help MSME players expand market reach and increase competitiveness through digital platforms, as well as assistance in obtaining halal certification and Business Identification Number (NIB) to strengthen business legality. The results of the activities show that this program has a positive impact on increasing the understanding of MSME players in utilizing digital technology and gaining wider access to the market. With halal certification and NIB, MSMEs also get better legal certainty and opportunities to develop in a more competitive business sector.